Convergence of libraries and technology organizations : new information support models - Barth, Christopher D (Oxford : Chandos, 2011)
The book provides an overview of how library and technology organisation have evolved and responded to the changes in economic and information system that have historically supported and defined them. This analysis creates a context for understanding the market forces in play that create an environment conducive for convergence in information organizations.
Includes bibliographical references and index.
uaj 08/05/13
Loans
Keywords: Academic libraries -- Information technology -- Management; Information technology -- Management; Academic libraries -- Automation; Library information networks